Optimization of hybrid energy management system based on high-energy solid-state lithium batteries and reversible fuel cells - Li, Xue; Li, Minghai; Habibi, Mostafa; Najaafi, Neda; Safarpour, Hamed (Energy (Oxford), 2023)
Integrating a high power source, like a super capacitor (SCAP), and a lithium-ion battery (LIB) for electric vehicle (EV) applications yields achievement improvements, including maximum reliability, long lifetime (LT), small size, and competitive pricing for the overall source. A hybrid energy storage system (ESS) controlled by an intelligent energy management strategy (EMS) may be substantially included in multi-source EV design and development. Therefore, this paper proposes a hybrid chimp optimization algorithm (ChOA) and Levy walk technique to create an optimum EMS. The proposed technique reduces battery power (BP) stress and increases the LT, which is accomplished by using a hybrid ChOA-Levy walk (ChOA-LW) optimization algorithm with a rule-based approach in accordance with understanding the performance of LIB and SCAP. In order to optimize the rule-based EMS's control settings, the latter strategy is suggested. The control approach can be implemented online once the offline optimization procedure is finished. The presented technique is evaluated via simulation and on an experimental platform by means of a power emulator testbed of a LIB/SCAP hybrid ESS. In terms of BP stress and LT, the findings are compared with a conventional rule-based approach and a mono-source containing a regular high-power LIB. Results obtained demonstrate the effectiveness of the suggested technique, which enables the requested performance to be satisfied with better energy utilization. The assessment results also show notable LT improvements for the LIB, an improvement of up to 19% over the mono-source in reference to a conventional single cell LIB. •A hybrid ChOA and Levy walk technique to create an optimum energy management strategy.•Reduce battery power stress and increase the long lifetime of the battery.•Presenting an experimental platform by means of a power emulator testbed of a lithium-ion battery hybrid energy storage system.•An improvement of up to 19% over the mono-source in reference to a conventional single-cell lithium-ion battery.